Motivational Factors and Constraints of Dairy farmers trained by Krishi Vigyan Kendra - Beerannavar, Basavaraj; Raghuraja, J (Journal of Agricultural Extension Management, 2018)
The study was conducted in Shivamogga district of Karnataka state to analyse the motivational factors, constraints and to enlist suggestions of farmers trained on dairy management practices by KVK, Shivamogga. In all 120 trained farmers from 12 villages constituted the sample for the study. The findings revealed that the factors viz., to increase income from dairy by learning new practices (76.66%), to have contact with the extension agency (55.00%), to get self-employment by attending training programmes (44.16%) motivated the respondents to attend the training. The trained farmers expressed that constraints such as, financial problems (71.67%), shortage of green fodder during summer season (59.17%), low price for the milk (44.17%) and inadequate veterinary services (39.17%) are adversely effecting the dairy enterprise. Majority of KVK trained farmers sought more number of extension activities to be organized based on the needs of the farmers (75%), followed by, remunerative price for milk (72.50%).